2012
DOI: 10.1093/cid/cis824
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Clinically Significant Drug–Drug Interaction in Healthy Volunteers Between the Hepatitis C Virus Protease Inhibitor Boceprevir and the HIV Integrase Inhibitor Raltegravir

Abstract: NCT01288417.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…Pharmacokinetic/pharmacodynamic (PK/PD) interactions between ART, immunosuppressive drugs, and anti-HCV drugs are frequent [42][43][44][45]. As ritonavir and cobicistat are strong CYP450 inhibitors that can increase many times the AUC of calcineurin inhibitors (ciclosporin and tacrolimus), Efavirenz, a modest CYP450 inducer, has been the preferred antiretroviral for many years [8][9][10].…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic/pharmacodynamic (PK/PD) interactions between ART, immunosuppressive drugs, and anti-HCV drugs are frequent [42][43][44][45]. As ritonavir and cobicistat are strong CYP450 inhibitors that can increase many times the AUC of calcineurin inhibitors (ciclosporin and tacrolimus), Efavirenz, a modest CYP450 inducer, has been the preferred antiretroviral for many years [8][9][10].…”
Section: Challengesmentioning
confidence: 99%
“…Other major PK/PD interactions have been recognized with the HCV NS3/4A PIs boceprevir and telaprevir [42,44,45]. These drugs had significant and non-predictable interactions with antiretrovirals, particularly non-NRTIs and HIV PIs, thus precluding many combinations.…”
Section: Challengesmentioning
confidence: 99%
“…95 In contrast, raltegravir may be used with both HCV agents without dosage adjustment. 96,97 Both antiretrovirals and current HCV treatment have multiple adverse effects. For instance, pegylated interferon and ribavirin have toxic effects that overlap with those of zidovudine and efavirenz, resulting in additive anemia and CNS effects, including depression, mood changes, and suicidality.…”
Section: Hepatitis Cmentioning
confidence: 99%
“…The protease inhibitor BOC decreased the exposure of all protease inhibitors; ATV/ritonavir did not significantly affect BOC exposure, whereas BOC was reduced by 45% and 32% when co-administered with LPV/ritonavir and DRV/ritonavir, respectively [75] . In a recent study no significant drug interaction between BOC and raltegravir was found in healthy volunteers [76] . The role of ritonavir in the drug interactions between TPV and ATV was recently investigated.…”
Section: Art Management In Hiv/hcv Coinfected Patients During Treatmementioning
confidence: 92%